Integrating SAR-ADC in GaN-Based Totem Pole PFC: A Step Toward Smart Power Conversion - Xu Cheng (IEEE Access)
This research investigates whether Successive Approximation Register Analog-to-Digital Converters (SAR-ADCs) might be included in (PFC) converters constructed to improve control precision and power conversion efficiency. The suggested approach enhances real-time voltage and current measurement using the high-speed capabilities of SAR-ADCs. This lets the converter’s operating parameters alter dynamically. Using a Proportional-Integral (PI) approach, a novel control algorithm has been created to optimize the duty cycle and switching frequency consistent with the instantaneous power needs. MATLAB/Simulink simulations have shown significant increases in efficiency and power factor under a variety of load scenarios. The real data supporting the simulation findings is proof of the practical usage of SAR-ADC in improving the performance of GaN-based PFC systems. The findings of the research suggest that power electronics might be opened by adding current ADC technology into more smart and more efficient energy solutions. This integration not only solves the issues now being faced in power factor correction but also prepares the system to manage future developments in smart power control.